Contribuição da produção animal em assentamentos da reforma agrária no estado de Mato Grosso - Vargas, Maurício Arantes (2014)
The economic viability of Agrarian Reform in Brazil can be related to the expanding of the amount of productive land, generating employment and income of settled families. The social viability, among other factors, is satisfied with the viability of housing and the possibility of the seated to rescue its socioeconomic dignity through its own work. The efficiency of agrarian reform is associated with earth observation in fulfill its social and economic role. In the consolidated property, the producer meets the basic needs of the family and generates surplus in an ongoing process of sustainability. Contextualization that agrarian reform has advanced is presented in Chapter 01, but lower than society and the settler aims. The farmer's family foundation is the main actor in this scenario and actively interact, overcoming difficulties or succumbing to adversity. The objectives of this work are presented in Chapter 02. In Chapter 03, the sources of income of settled families and the factors that may contribute to the consolidation of the properties are identified. The location of the settlement, the size of the properties, the occupation time, the activities developed and the structure of the basic cell, contributed to the observed socioeconomic outcomes. There were used a multivariate analysis, using the technique of Principal Component and Analysis Hierarchical of Cluster to establish the main trends that prevailed in these settlements and obtain homogeneous groups who expressed great heterogeneity experienced in the studied properties. There have been cases where the external and farm income were more important contrasting with properties, where the income from livestock, especially dairy cattle, was the main source of family resources. In Chapter 04 gave emphasis to the contribution of animal production in the consolidation of settlements. The Dairy Farming was important in 91.67% of the studied properties. There was difference in the efficiency of dairy cattle may be associated with production scale, the farmer specificity and the structuring of the base cell. It was verified the feasibility and potential of the dairy activity in the consolidation of the agrarian reform settlements in the state of Mato Grosso.